Federal State Educational Standards of Higher Education: New Characteristics of Professionally Oriented Foreign Language Teaching in Students of Non-Linguistic Universities - N. L. Baydikova (Научный диалог)
The article reveals changes of the essential characteristics of professionally oriented teaching students of non-linguistic universities of foreign language, that are related to the adoption of the Federal state educational standards of higher education. The author offers a brief excursion into the history of the issue in our country and abroad. A review of domestic studies on professionally oriented teaching of foreign language in accordance with the standards of the previous generation. As a result of generalization the features of professionally-oriented foreign language teaching are revealed in the state educational standards of higher professional education: narrow professional focus, interdisciplinary connections, special methodological support. Special attention is paid to the influence of new educational standards on the content of professionally-oriented training. The article shows that the determining factor is the status of foreign language competence for non-linguistic specialties, namely it belonging to the group of common cultural competences. The novelty of the study is in determining the characteristics of professionally oriented teaching non-linguistic students of foreign language in accordance with Federal state educational standards of higher education: general professional / general scientific orientation, the formation of general learning abilities in the context of person-centered learning. The author puts in perspective the task of developing the means and methods of teaching non-linguistic students of foreign language in accordance with the modern understanding of professionally-oriented training.